A qualitative exploration of health student perspectives of rural and remote placements during the early stages of the COVID‐19 pandemic. (29th November 2022) - Sheepway, Lyndal; Jessup, Belinda; Podubinski, Tegan; Heaney, Susan; Bailie, Jodie; Hoang, Ha; Bourke, Lisa
Abstract: Objective: To explore health student perspectives of rural and remote placements during the early stages of the COVID‐19 pandemic. Setting: Australia. Participants: Allied health, nursing and medical students with a planned rural or remote placement between February and October 2020. Design: Semi‐structured interviews ( n  = 29) with data thematically analysed. Results: Five main themes emerged from student experiences: (1) 'Do we go? Don't we go? Like how much risk is involved?' related to student concerns regarding acquiring and transmitting COVID‐19 on placement; (2) 'We are sort of just standing at the door trying to watch' encompassed student perceptions of missed clinical learning opportunities in response to health and safety measures related to COVID‐19; (3) 'I, as a student, sort of fell under the radar' related to student perceptions of suboptimal supervision; (4) 'It was a bit more difficult to engage with that wider community' recognised student feelings of social disconnection and their lack of opportunity for community immersion; and (5) 'We felt like we got something that is more than we expected' emerged from student reflections on training during the pandemic and alternative placements (virtual, simulated and non‐clinical) that exceeded expectations for learning. Conclusions: Although most students were willing and able to undertake their rural or remote placement in some form during the early stages of the pandemic and identified unanticipated learning benefits, students recognised lost opportunities to build clinical skills, become culturally aware and connect with rural communities. It remains unknown how these rural and remote placement experiences will impact rural intention and in turn, rural workforce development.